Willingness to disclose child maltreatment: CSA vs other forms of child abuse in relation to gender. (May 2018) - Lev-Wiesel, Rachel; First, Maya
Abstract: The aim of the study was to examine the role of gender in willingness to disclose childhood sexual abuse (CSA) compared to other forms of abuse (physical, emotional and neglect) in young adolescents. Willingness was examined through two terms: reluctance— the level of unwillingness or disinclination to disclose, and urge—the need to share in order to get rid of unbearable feelings. The sample consisted of 3, 156 boys (n = 1, 544) and girls (n = 1, 612) between the ages of 11–16 who reported having been abused at least once during their life. Participants were divided into three groups: experiencing other than CSA, sexual abuse with no physical contact, and sexual abuse with physical contact. Regarding measures, a self-report questionnaire incorporating the following instruments was administered: Demographics, the Juvenile Victimization Questionnaire (JVQ), and the Disclosure of Trauma Questionnaire (DTQ). Study results indicated that CSA victims were more reluctant to disclose than victims of other than CSA forms of abuse. The more severe the CSA (physical contact) the lower was the willingness to disclose. Boys were more reluctant than girls to disclose sexual abuse whether or not it involved physical contact. Reluctance to disclose was positively associated with emotional reactions to disclosure while urge to talk was negatively correlated with emotional reactions to disclosure.